2019
DOI: 10.1007/s42770-019-00120-3
|View full text |Cite
|
Sign up to set email alerts
|

A common vaginal microbiota composition among breeds of Bos taurus indicus (Gyr and Nellore)

Abstract: Describing the bovine vaginal microbiota is essential to better understand its physiology and its impact on health maintenance. Despite the economic importance of reproduction of these animals, bovine vaginal microbial community is still poorly described in comparison with rumen microbiome. Previous studies of our group described the vaginal microbiota of Nellore, an important Bos taurus indicus breed, using metagenomics. In order to better understand this microbiota, the present work aims to investigate anoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 41 publications
5
20
0
1
Order By: Relevance
“…These reports match with the present nding of bacterial community identi ed in CVM of buffalo. On the other hand, major bacterial genera in the vagina of Gyr and Nellore breed cows include Aeribacillus, Bacillus, Clostridium, Bacteroides and Ruminococcus (Giannattasio-Ferraz et al 2019). The present analysis also depicted the presence of Bacillus spp.…”
Section: Discussionsupporting
confidence: 49%
“…These reports match with the present nding of bacterial community identi ed in CVM of buffalo. On the other hand, major bacterial genera in the vagina of Gyr and Nellore breed cows include Aeribacillus, Bacillus, Clostridium, Bacteroides and Ruminococcus (Giannattasio-Ferraz et al 2019). The present analysis also depicted the presence of Bacillus spp.…”
Section: Discussionsupporting
confidence: 49%
“…Such bacteria at the phylum level specifically comprised Firmicutes, Bacteroidetes, and Proteobacteria [22,29] as depicted in Figure 2, and that constitute about 30-40% of the total bacteria present in the vaginal niche [30]. Recent studies by Giannattasio-Ferraz et al [31] have also revealed…”
Section: Vaginal Microfloramentioning
confidence: 90%
“…Such bacteria at the phylum level specifically comprised Firmicutes, Bacteroidetes, and Proteobacteria [22,29] as depicted in Figure 2, and that constitute about 30-40% of the total bacteria present in the vaginal niche [30]. Recent studies by Giannattasio-Ferraz et al [31] have also revealed a substantial similarity existing between the vaginal microbiota of Nellore cattle and Gyr (which is also another essential breed) and the main bacterial species described were mainly Aeribacillus, Bacillus, Clostridium, Bacteroides, and Ruminococcus. Mycosphaerella was the dominant fungus in this microbiota, while Archaea were poorly represented, and Methanobrevibacter were the most common.…”
Section: Vaginal Microfloramentioning
confidence: 96%
“…Recently, two new Corynebacterium, C. urogenitale and C. endometrii, were described, both isolated from the bovine vaginal tract and nonpathogenic for uterine epithelial cells [35,36]. Evidence suggests that many Corynebacterium species are commensal members of the uterine microbiome of cattle [37][38][39][40] and buffalo [41]. Evidence of the SpaD-type pili system (Table 1) conserved among the C. phoceense strains suggests that adhesion is central to its survival.…”
Section: Discussionmentioning
confidence: 99%